Knowledge, awareness and preparedness regarding coronavirus disease 2019 pandemic among community pharmacy practitioners working in Kathmandu, Nepal: A pilot study - Sunil Shrestha; Nisha Jha; Subish Palaian; Pathyil Ravi Shankar (SAGE Open Medicine, 2020)
Good knowledge, awareness and preparedness regarding coronavirus disease 2019, among community pharmacy practitioners (CPPs), will enable them to provide correct information and support to patients, convey instructions from the public health authorities and protect their own health. Objective: The aim of this study was to determine knowledge, awareness and preparedness regarding coronavirus disease 2019 among CPPs working in Kathmandu, Nepal. Methods: A cross-sectional study was conducted using a convenience sampling method from 10 February to 25 March 2020. Data were analysed descriptively, and one-sample independent t-test and one-way analysis of variance were used to compare scores among different subgroups of respondents ( p  < 0.05). Post hoc analyses (following analysis of variance) were done using the Bonferroni test. Results: A total of 81 CPPs participated. Mean ± standard deviation age was 26.70 ± 5.29 years. Majority of the respondents were male (64.2%). Many CPPs (40.7%) had work experience between 1 and 5 years. Almost half (45.7%) had an educational qualification of Diploma in Pharmacy. Significant differences in knowledge ( p  = 0.022) and preparedness ( p  < 0.001) were found among individuals with differing levels of work experience. Similarly, a significant difference was found between knowledge-preparedness and work experience ( p  = 0.022 and p  < 0.001), location of pharmacy ( p  < 0.001) and educational qualification ( p  = 0.031). Awareness ( p  < 0.001) and preparedness scores ( p  = 0.049) were different among community pharmacies with the different number of medicines available. Conclusion: Knowledge was found to be higher in CPPs with a work experience of more than 5 years. CPPs working at larger community pharmacies were more aware and prepared. CPPs’ knowledge, awareness and preparedness should be evaluated more widely and strengthened.